The role of the Ebro Block on the deformation experienced within the Pyrenean realm: Insights from deformable plate tectonic models. (March 2023) - King, Michael T.; Welford, J. Kim; Tugend, Julie
Abstract: Plate kinematic models of the Pyrenees have been extensively debated due to discrepancies between plate kinematic constraints for the Iberian plate and Atlantic/Tethyan related plate motions. Recently, the morphology of the Iberian plate and its partitioning into several continental blocks has been proposed as a solution towards reconciling discrepancies between previously published reconstructions that treat Iberia as a single, rigid, tectonic plate. Herein, the first deformable plate tectonic modeling study of the Pyrenean realm is presented using previously published and newly presented reconstructions of Iberia. Special emphasis is given to the kinematics of the Ebro Block, a continental block situated between the Pyrenees and Iberian Ranges, whose kinematics are considered to play a key role in the extensional deformation experienced within the Pyrenean realm. Temporal variations in strain rate and crustal thickness calculated by deformable plate models provide insights regarding the pre-orogenic template of the Pyrenees and the variability in regional stress directions along the Iberia-Eurasia plate boundary from the Triassic to Cenomanian. Models that propose transtensional rift phases within the Pyrenean realm induced by the Landes High and Ebro Block kinematics since the Triassic are successful in deriving crustal thicknesses indicative of a pre-orogenic hyperextended rifted margin within the Pyrenean realm. The results of this study demonstrate the importance of continental block kinematics during rift-related deformation and their impact on the evolution and partitioning of rift domains. Furthermore, this study also highlights potential avenues to consider for improving future plate kinematic models of Iberia, and regions elsewhere.